Empirical investigation of the nexus between tax audit and taxpayers’ compliance in South West, Nigeria (Journal of Namibian Studies : History Politics Culture, 2023)
This study investigated the nexus between tax audit and taxpayers’ compliance in South West, Nigeria. The study adopted a descriptive survey design with the aid of a structured questionnaire to elicit the needed information from the respondents. The population, which equally represented the sample size was all the 93 Audit and Administrative staff of the headquarters of the State Board of Internal Revenue Service (SBIR) of Ekiti, Osun and Oyo States. Descriptive and inferential statistics were used to analyse data. The hypothesis was tested with Pearson Correlation and multiple linear regression. The result indicated that tax audit has a positive and significant effect on both the voluntary and non-voluntary taxpayer’s compliance in Southwest, Nigeria with their respective coefficient and significant values of 0.672 and 0.000